Marine fog : challenges and advancements in observations, modeling, and forecasting - Koračin, Darko; Dorman, Clive E. (Springer, 2017)
This volume presents the history of marine fog research and applications, and discusses the physical processes leading to fog's formation, evolution, and dissipation. A special emphasis will be on the challenges and advancements of fog observation and modeling as well as on efforts toward operational fog forecasting and linkages and feedbacks between marine fog and the environment.
Includes index.
Keywords: Fog.; elektronické knihy; electronic books